Ecovention : Current art to transform ecologies - Spaid, Sue; Desmarais, Charles; Contemporary Arts Center, Cincinnati (Cincinnati : Contemporary Arts Center Cincinnati, 2002)
AMD & ART ; Bayer, Herbert ; Beaumont, Betty ; Beuys, Joseph ; Brookner, Jackie ; Chin, Mel ; Damon, Betsy ; Denes, Agnes ; Dietzler, Georg ; Feynman, Richard ; Haacke, Hans ; Hakansson, Henrik ; Harrison, Newton ; Honer, Michael ; Hull, Lynne ; Irland, Basia ; Johanson, Patricia ; Laderman Ukeles, Mierle ; Leibovitz Steinman, Susan ; Lundquist, Laurie ; Miller, Kathryn ; Ngo, Viet ; Nine Mile Run Greenway Project ; Ocean Earth Development Corporation ; Rahmani, Aviva ; Simpson, Buster ; Smithson, Robert ; Sonfist, Alan ; Steinmann, George ; Superflex ; Zakai, Shai
A short history of ecoventions p. 133-136
Artist's philosophical statements p. 137-144
glossary of eco-terms p. 145-146
Engels
Ecovention : Current art to transform ecologies, Contemporary Arts Center Cincinnati, 09.06 - 18.08.2002
boek